NiCuZn material with high saturation magnetic flux density and preparation method thereof
By accurately blending the proportions of the main components and additives of the NiCuZn material, the magnetic permeability and saturation magnetic induction intensity of the material are optimized, which solves the problem that existing materials are difficult to have both high magnetic permeability and high saturation magnetic flux density at the same time, and improves the material's resistivity and Curie temperature, enabling efficient high-frequency, high-power application performance.
Patent Information
- Application Number
- CN202411521188.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing nickel-zinc ferroferric materials to have both high magnetic permeability and high saturation flux density, and the Curie temperature and resistivity of NiCuZn materials are low, resulting in poor stability.
By accurately blending the proportions of the main components and additives of the NiCuZn material, the ratio of Fe2O3, ZnO, NiO, CuO and Mn3O4 is optimized, and glass powder, talc powder, titanium dioxide, yttrium oxide and tin oxide are added as additives to improve the magnetic properties of the material. Conductivity, saturation magnetic induction, resistivity and Curie temperature.
It realizes the excellent magnetic properties and thermal stability of the material in high-frequency and high-power applications, improves the comprehensive performance of the material, and meets the needs of electronic products developing towards high performance and miniaturization.
Smart Images

Figure BDA0005108081570000061 
Figure BDA0005108081570000071 
Figure BDA0005108081570000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electronic materials, and in particular to a high saturation magnetic flux density NiCuZn material and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics industry, electronic products are moving towards high speed, high sensitivity, miniaturization and high frequency. Under this trend, the power inductors inside electronic products also need to be miniaturized accordingly to adapt to a more compact space layout. However, miniaturized power inductors need to carry higher rated currents when working, which puts more stringent requirements on the performance of its main raw material, nickel-zinc ferrite. Existing nickel-zinc ferrite materials can only choose between high magnetic permeability and high saturation magnetic flux density, and it is difficult to have both of these two key material properties at the same time. This limits the performance improvement of miniaturized power inductors to a certain extent and becomes a bottleneck for the further development of the electronics industry. In addition, the NiCuZn material in the prior art has a low Curie temperature and resistivity, resulting in poor stability. Therefore, how to develop a NiCuZn material that can simultaneously meet high magnetic permeability and high saturation magnetic flux density and high stability has become a problem that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present application is to overcome the above technical problems and provide a high saturation magnetic flux density NiCuZn material and a preparation method thereof.
[0004] The present application provides a high saturation magnetic flux density NiCuZn material, the high saturation magnetic flux density NiCuZn material comprises a main component and an additive, the main component comprises Fe2O350.5-53.0mol%, ZnO 21.5-23.5mol%, NiO22.5-24.5mol%, CuO 0.5-1.3mol%, Mn3O4 0.5-2.2mol%; Based on the weight of the main component, the additives include: 0.10-0.30wt% glass powder, 0.01-0.10wt% talc powder, 0.05-0.10wt% titanium dioxide, 0.01-0.05wt% yttrium oxide, and 0.05-0.10wt% tin oxide.
[0005] By adopting the above technical solution, the present application aims to significantly improve a number of key properties of NiCuZn materials, including initial magnetic permeability, saturation magnetic induction intensity, resistivity and Curie temperature, by accurately adjusting the ratio of the main components and additives, thereby effectively solving the challenges faced by the prior art. The present application can significantly improve the initial magnetic permeability of the material by optimizing the ratio of the main components, especially the precise regulation of Fe2O3, ZnO, NiO, CuO and Mn3O4, combined with trace amounts of glass powder, talcum powder, titanium dioxide, yttrium oxide and tin oxide additives. High initial magnetic permeability means that the material can respond quickly at low magnetic field strength and achieve a higher magnetic flux density, which is particularly important for high-frequency applications. In high-frequency circuits, high initial magnetic permeability can reduce signal delays, improve signal processing speed and efficiency, thereby meeting the needs of electronic products to develop towards high speed and high sensitivity. In addition, the appropriate addition of glass powder and yttrium oxide in the present application, they work together on the microstructure of the material, promote grain growth, and form a denser lattice structure, thereby greatly improving the saturation magnetic induction intensity of the material without sacrificing other properties. High saturation magnetic induction allows the material to maintain good magnetic properties under high-intensity magnetic fields, which is crucial for miniaturized power inductors that carry higher rated currents, ensuring the stability and reliability of the material under high current density. In high-frequency applications, the high resistivity of the material can effectively reduce eddy current losses and improve energy conversion efficiency. By introducing trace amounts of glass powder and yttrium oxide, the present application not only optimizes the microstructure of the material, but also increases the resistivity of the material, reduces energy loss under high frequencies, and thus improves the energy efficiency and service life of electronic components. The Curie temperature is the critical temperature at which a material changes from ferromagnetism to paramagnetism. Through the technical solution of the present application, the Curie temperature of the material can be significantly increased, mainly due to the addition of yttrium oxide, which can enhance the thermal stability of the material and ensure that the material can still maintain its magnetic properties under high temperature environments, thereby broadening the application range of the material, especially in electronic equipment and systems under high temperature environments, such as automotive electronics, industrial heating equipment, etc. In summary, the technical solution of this application not only solves the performance balance problem between high magnetic permeability and high saturation magnetic flux density by precisely controlling the ratio of the main component and the additive, but also improves the resistivity and Curie temperature of the material, providing an ideal material solution for high-frequency and high-power applications. This innovation not only optimizes the performance of the material, but also improves the energy efficiency and reliability of electronic products, providing strong technical support for the development of the electronics industry towards higher performance and smaller size.
[0006] Optionally, the weight ratio of the Fe2O3 to the ZnO is 2.2-2.4:1.
[0007] By adopting the above technical solution and using a weight ratio of Fe2O3 to ZnO of 2.2 to 2.4:1, the magnetic properties of the material can be significantly optimized. Specifically, this ratio not only ensures that the material has sufficient magnetic permeability to reduce high-frequency losses and improve signal transmission efficiency, but also ensures that the material has a high saturation flux density, so that it can still maintain good magnetic properties under high current density, thereby improving the performance of the material in high-frequency and high-power applications. In addition, this optimized ratio also helps to improve the thermal stability and mechanical strength of the material, ensure the stability and reliability of the material in complex environments, and provide strong technical support for the high performance and miniaturization design of electronic products. In summary, by precisely controlling the weight ratio of Fe2O3 to ZnO, the technical solution of this application not only solves the performance balance problem between high magnetic permeability and high saturation flux density, but also improves the comprehensive performance of the material, providing an ideal material solution for high-frequency and high-power applications, and promoting the development of the electronics industry towards higher performance and miniaturization.
[0008] Optionally, the weight ratio of the Fe2O3 to the ZnO is 2.3:1.
[0009] Optionally, based on the weight of the main component, the additives include: 0.20wt% glass powder, 0.05% talc powder, 0.08wt% titanium dioxide, 0.04wt% yttrium oxide, and 0.08wt% tin oxide.
[0010] By adopting the above technical solution, by accurately setting the content of additives glass powder, talcum powder, titanium dioxide, yttrium oxide and tin oxide, the present application aims to solve the performance bottleneck faced by traditional NiCuZn materials in high-frequency and high-power applications, especially to optimize the magnetic properties, thermal stability and processing performance of the materials. In high-frequency and high-power applications, NiCuZn materials need to have high magnetic permeability, high saturation magnetic flux density, good thermal stability and processing performance at the same time. However, there is often a trade-off between these properties in traditional materials, and it is difficult to achieve the best at the same time. For example, high magnetic permeability may be accompanied by a lower saturation magnetic flux density, or the thermal stability of the material is not enough to cope with temperature changes in high-power applications. In addition, the lack of processing performance may also limit the wide application of materials. The addition of glass powder, talcum powder, titanium dioxide, yttrium oxide and tin oxide can improve the microstructure of the material, promote grain refinement, and thus improve the magnetic permeability and saturation magnetic flux density of the material. Especially in high-frequency applications, the optimized magnetic properties can reduce signal delay and improve energy conversion efficiency. In summary, by setting the content of glass powder, talcum powder, titanium dioxide, yttrium oxide and tin oxide, the technical solution of the present application not only solves the bottleneck problem of material performance in high-frequency and high-power applications, but also significantly improves the comprehensive performance of the material, and provides strong technical support for the miniaturization, high performance and high energy efficiency of electronic components, and promotes the development of the electronics industry towards higher performance and smaller size.
[0011] In a second aspect, the present application provides a method for preparing a NiCuZn material with a high saturation magnetic flux density, characterized in that the preparation method comprises the following steps: The main components and additives are mixed according to the formula ratio, wet sand milling is performed to obtain a mixture, the mixture is pre-sintered, and then secondary sand milling is performed to obtain a slurry. After the slurry is spray granulated and formed, it is sintered to obtain the high saturation magnetic flux density NiCuZn material.
[0012] By adopting the above technical solution, the high saturation flux density NiCuZn material of the present application not only exhibits excellent magnetic properties, including high magnetic permeability and high saturation flux density, but also has good thermal stability and processing performance, meeting the stringent requirements of high-frequency and high-power application fields for material performance. In addition, the optimization of the entire preparation process also effectively improves the consistency and yield rate of materials, reduces production costs, provides strong support for the miniaturization and high performance of electronic components, and promotes the development of the electronics industry to a higher level.
[0013] Optionally, the pre-sintering treatment temperature is 950-1000°C.
[0014] By adopting the above technical solution and using a pre-sintering temperature of 950-1000°C, not only the initial chemical reaction and microstructure optimization of the material are promoted, but also impurities are effectively removed, creating the best conditions for the subsequent sintering process. The implementation of this technical solution significantly improves the preparation quality and efficiency of high saturation flux density NiCuZn materials, ensures that the material exhibits excellent magnetic properties in high-frequency and high-power applications, and reduces production costs, reflecting the technological innovation and optimization in materials science and engineering practice.
[0015] Optionally, the pre-firing treatment temperature is 980°C.
[0016] Optionally, the slurry has a solid content of 60-66%, a slurry viscosity of 200-300 mPa·s, and a particle size D50 of 0.5±0.1 μm.
[0017] By adopting the above technical solution, this application significantly optimizes the sintering performance, microstructure and magnetic properties of high saturation flux density NiCuZn materials by controlling the particle size after secondary sand grinding to D50 = 0.5 ± 0.1 μm, ensuring that the material exhibits excellent performance in high-frequency and high-power applications, while improving production efficiency and finished product quality, reflecting the precision control and optimization strategy in materials science and engineering practice. The implementation of this technical solution provides strong support for promoting the miniaturization, high performance and energy saving of electronic components.
[0018] Optionally, the sintering treatment temperature is 1200-1300°C.
[0019] By adopting the above technical scheme, within this temperature range, a more sufficient solid phase reaction occurs between the components such as Fe2O3, ZnO, NiO, CuO and Mn3O4 in the material to form a stable compound, laying a solid structural foundation for the high saturation flux density of the material. Moderate high temperature sintering helps the growth and rearrangement of grains to form a more uniform and dense microstructure, which is crucial to improving the magnetic properties of the material. Too high a temperature may cause excessive grain growth, which in turn reduces the performance of the material; while too low a temperature may cause incomplete sintering, affecting the density and strength of the material. At a temperature of 1200-1300°C, the gas and residual impurities in the material can be fully released, which helps to reduce the porosity, increase the density of the material, and thus improve its mechanical strength and magnetic properties. In summary, the sintering treatment temperature of 1200-1300°C not only promotes the solid phase reaction and microstructure optimization of the material, but also effectively controls the porosity and density of the material, ensuring that the high saturation flux density NiCuZn material exhibits excellent magnetic properties and mechanical strength in high-frequency and high-power applications. The implementation of this technical solution not only improves the performance of the material, but also optimizes production efficiency and reduces energy consumption, reflecting the technological innovation and sustainable development strategy in materials science and engineering practice.
[0020] Optionally, the sintering treatment temperature is 1250°C.
[0021] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The present application provides a high saturation flux density NiCuZn material, which solves the technical problem of the difficulty in balancing high magnetic permeability and high saturation magnetic flux density of traditional NiCuZn materials by precisely controlling the molar ratio of the main components. This optimized combination not only significantly improves the saturation magnetic flux density of the material, but also maintains good magnetic permeability, so that the material performs well in high-frequency and high-power applications. The core of this application is to propose an innovative high saturation magnetic flux density NiCuZn material, which aims to solve the performance balance problem of traditional NiCuZn materials in the pursuit of high magnetic permeability and high saturation magnetic flux density. Through carefully designed material formula and preparation process, the material has shown excellent performance in high-frequency and high-power applications. The main components are Fe2O3, ZnO, NiO, CuO and Mn3O4. Fe2O3, as a magnetic main body, is responsible for providing the basic magnetic properties of the material; the introduction of ZnO and NiO not only enhances the stability of the material, but also plays a key role in improving the saturation magnetic flux density; the presence of CuO helps to improve the resistivity and thermal stability of the material. By fine-tuning the molar ratio of each component, the dual optimization of the material's magnetic permeability and saturation flux density is achieved, breaking through the limitations of traditional material performance. Mn3O4 can optimize the material's microstructure and magnetic properties and improve the material's saturation flux density. Although trace amounts of glass powder, talcum powder, titanium dioxide, yttrium oxide and tin oxide are additives, they play an important role. The addition of glass powder promotes the optimization of the material's microstructure, enhances the bonding force between particles, reduces grain boundary defects, and thus indirectly improves the material's magnetic properties. As an efficient dopant, yttrium oxide can significantly increase the material's Curie temperature and enhance the material's magnetic stability in a high temperature environment. It also has a positive effect on improving the material's resistivity and reduces losses under high-frequency working conditions. In summary, the high saturation flux density NiCuZn material provided in this application has successfully achieved the goal of significantly increasing the saturation flux density while maintaining good magnetic permeability by precisely controlling the molar ratio of the main components and rationally adding additives. This material not only exhibits superior performance in high-frequency and high-power applications, such as stable magnetic permeability, high saturation magnetic flux density, low loss and good thermal stability, but also has high resistivity and Curie temperature, which greatly broadens its application range in modern electronic devices and provides strong support for promoting the electronics industry to develop towards higher performance and smaller size. Through the technical solution of the present invention, we not only solve the challenges of traditional NiCuZn materials in performance balance, but also open up new possibilities for the optimized design of high-frequency electronic components, marking another major progress in the field of electronic materials science.
[0022] 2. The high saturation flux density NiCuZn material of the present application not only exhibits excellent magnetic properties, including high magnetic permeability and high saturation flux density, but also has good thermal stability and processing performance, meeting the stringent requirements of high-frequency and high-power application fields for material performance. In addition, the optimization of the entire preparation process has effectively improved the consistency and yield rate of the material, reduced production costs, provided strong support for the miniaturization and high performance of electronic components, and promoted the development of the electronics industry to a higher level. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments. Specific embodiments
[0024] Example 1 The present embodiment provides a high saturation magnetic flux density NiCuZn material, the high saturation magnetic flux density NiCuZn material includes a main component and an additive, the main component includes Fe2O350.5mol%, ZnO 21.5mol%, NiO 24.5mol%, CuO1.3mol%, Mn3O4 2.2mol%; Based on the weight of the main component, the additives include: 0.10wt% glass powder, 0.01wt% talc powder, 0.05wt% titanium dioxide, 0.01wt% yttrium oxide, and 0.05wt% tin oxide.
[0025] The preparation method of the high saturation magnetic flux density NiCuZn material in this embodiment comprises the following steps: The main components and additives are mixed according to the formula ratio, and wet sand milling is performed for 2 hours to obtain a mixture, and the mixture is pre-sintered at a temperature of 950°C for 3 hours; then secondary sand milling is performed in sequence to obtain a slurry, the slurry has a solid content of 60%, a slurry viscosity of 200 mPa·s, and a particle size after secondary sand milling of D50=0.5±0.1 μm, the slurry is spray granulated, and the granulated particles are pressed through a mold on a powder molding machine to obtain a circular ring-shaped blank, the pressing pressure is set to 40 MPa, and the pressure is maintained for 3 minutes to ensure that the density of the circular ring-shaped blank is uniform, and the specifications of the blank are φ25×15×7.5 mm; the blank is transferred to a sintering furnace for sintering at a temperature of 1200°C for 2 hours, and after sintering, it is rapidly cooled to obtain a NiCuZn material with a high saturation magnetic flux density.
[0026] Embodiment 2-3 The difference between Examples 2 to 3 and Example 1 is that, when preparing the high saturation magnetic flux density NiCuZn material, the weight fractions of the materials of the various components are different. The differences are shown in Table 1.
[0027] Table 1 - Differences between Examples 2 to 3 and Example 1 Comparative Examples 1 to 7 Comparative Example 1 The difference between this comparative example and Example 2 is that the main components in this comparative example include Fe2O3 54.0 mol%, ZnO2 0.5 mol%, NiO 22.5 mol%, CuO 0.5 mol%, and Mn3O4 2.5 mol%; the rest is consistent with Example 2.
[0028] Comparative Example 2 The difference between this comparative example and Example 2 is that the main components in this comparative example include Fe2O349.0mol%, ZnO24.5mol%, NiO 22.5mol%, CuO 3.5mol%, and Mn3O4 0.5mol%; the rest is consistent with Example 2.
[0029] Comparative Example 3 The difference between this comparative example and Example 3 is that, in this comparative example, an equal amount of glass powder is used to replace yttrium oxide when preparing the high saturation magnetic flux density NiCuZn material.
[0030] Comparative Example 4 The difference between this comparative example and Example 3 is that, in this comparative example, when preparing the high saturation magnetic flux density NiCuZn material, an equal amount of yttrium oxide is used instead of glass powder.
[0031] Comparative Example 5 This comparative example provides NiCuZn materials with the brands DN45H, DN50T and DN50B produced by DMR Company.
[0032] Comparative Example 6 This comparative example provides NiCuZn materials with the brands TN35H, TN40H and TN50D produced by TDG Company.
[0033] Comparative Example 7 This comparative example provides NiCuZn materials with grades D1C and D25 produced by ACME.
[0034] Experimental testing The following performance tests were performed on the NiCuZn materials obtained in Examples 1 to 3 and Comparative Examples 1 to 7: Initial magnetic permeability μi: Under the condition of number of turns N = 20Ts, the initial magnetic permeability of the sample ring is tested using an HP-4284A LCR tester.
[0035] Saturation magnetic induction intensity Bs: Under the condition of turns N=20Ts, the saturation magnetic induction intensity Bs of the NiCuZn material core is tested using SY-8258 BH analyzer.
[0036] The experimental test results of Examples 1 to 3 and Comparative Examples 1 to 7 are shown in Table 2.
[0037] Table 2 - Experimental test results of Examples 1 to 3 and Comparative Examples 1 to 7 Result analysis: The difference between Examples 2 and 3 and Example 1 is that when preparing the high saturation magnetic flux density NiCuZn material, the weight fractions of the materials of each component are different. Combined with the experimental test data in Table 2, it can be seen that the high saturation magnetic flux density NiCuZn material prepared by Example 3 has better comprehensive performance, including initial magnetic permeability, saturation magnetic induction resistivity and Curie temperature.
[0038] The difference between comparative example 1 and example 2 is that the main components in this comparative example include Fe2O354.0mol%, ZnO20.5mol%, NiO 22.5mol%, CuO 0.5mol%, Mn3O4 2.5mol%; the rest is consistent with example 2. Compared with the main components in example 2, it is found that the amount of Fe2O3 is too much, while the amount of ZnO is too little. The difference between comparative example 2 and example 2 is that the main components in this comparative example include Fe2O349.0mol%, ZnO 24.5mol%, NiO 22.5mol%, CuO3.5mol%, Mn3O4 0.5mol%; the rest is consistent with example 2. Compared with the main components in Example 2, it is found that the amount of Fe2O3 is too small, while the amount of ZnO is too large. Combined with the experimental test data in Table 2, it can be seen that if the amount of Fe2O3 is too large or too small, or the amount of ZnO is too large or too small, the comprehensive performance of the obtained high saturation flux density NiCuZn material will be reduced.
[0039] The difference between Comparative Example 3 and Example 3 is that, in this comparative example, an equal amount of glass powder is used to replace yttrium oxide when preparing the high saturation magnetic flux density NiCuZn material.
[0040] The difference between Comparative Example 4 and Example 3 is that, in this comparative example, an equal amount of yttrium oxide is used instead of glass powder when preparing the high saturation magnetic flux density NiCuZn material.
[0041] Comparative Example 5 provides NiCuZn materials with the grades of DN45H, DN50T and DN50B of DMR Company. Comparative Example 6 provides NiCuZn materials with the grades of TN35H, TN40H and TN50D of TDG Company. Comparative Example 7 provides NiCuZn materials with the grades of D1C and D25 of ACME Company. Combined with the experimental test data in Table 2, it can be seen that the comprehensive performance of the high saturation flux density NiCuZn material prepared in the present application is better than that of the NiCuZn material in the prior art, especially the resistivity, Curie temperature, and saturation magnetic induction intensity are better than those of the NiCuZn material provided in the comparative example.
[0042] Embodiment 4-5 Example 4 The difference between this embodiment and embodiment 3 is that the total molar fraction of Fe2O3 and ZnO in this embodiment is 74 mol%, wherein the weight percentage ratio of Fe2O3 to ZnO is 2.2:1.
[0043] Example 5 The difference between this embodiment and embodiment 3 is that the total molar fraction of Fe2O3 and ZnO in this embodiment is 74 mol%, wherein the weight percentage ratio of Fe2O3 to ZnO is 2.4:1.
[0044] The experimental test results of Examples 4-5 are shown in Table 3.
[0045] Table 3 - Experimental test results of Examples 4 to 5 Result analysis: The difference between Examples 4 to 5 and Example 3 is that when preparing the high saturation magnetic flux density NiCuZn material, the total molar fraction of Fe2O3 and ZnO is 74wt%. Among them, the molar fraction ratio of Fe2O3 and ZnO is different. Combined with the experimental test results in Table 3, it can be seen that when the molar fraction ratio of Fe2O3 and ZnO is 2.3:1, the comprehensive performance of the high saturation magnetic flux density NiCuZn material is better.
[0046] Embodiment 6-7 Example 6 The difference between this embodiment and embodiment 3 is that when preparing the high saturation magnetic flux density NiCuZn material, the weight of the main component is used as the calculation basis, and the additives include: 0.20wt% glass powder, 0.05% talcum powder, 0.08wt% titanium dioxide, 0.04wt% yttrium oxide, and 0.08wt% tin oxide.
[0047] Example 7 The difference between this embodiment and embodiment 3 is that when preparing the high saturation magnetic flux density NiCuZn material, the weight of the main component is used as the calculation basis, and the additives include: 0.30wt% glass powder, 0.10wt% talcum powder, 0.10wt% titanium dioxide, 0.05wt% yttrium oxide, and 0.10wt% tin oxide.
[0048] The experimental test results of Examples 6-7 are shown in Table 4.
[0049] Table 4 - Experimental test results of Examples 6 to 7 Result analysis: The difference between Examples 6 to 7 and Example 3 is that when preparing the high saturation magnetic flux density NiCuZn material, the amount of additives added is different. Combined with the test data provided in Table 4, it can be seen that the comprehensive performance of the high saturation magnetic flux density NiCuZn material prepared by Example 6 is better.
[0050] Example 8 The difference between this embodiment and embodiment 6 is that when preparing the high saturation magnetic flux density NiCuZn material, the preparation method of the high saturation magnetic flux density NiCuZn material includes the following steps: The main components and additives are mixed according to the formula ratio, wet sand milling is performed for 2 hours to obtain a mixture, and the mixture is pre-sintered at a temperature of 980°C for 3 hours; secondary sand milling is performed in sequence to obtain a slurry, the slurry has a solid content of 63%, a slurry viscosity of 250 mPa·s, and a particle size after secondary sand milling of D50=0.5±0.1 μm; the slurry is spray granulated, and the granulated particles are pressed through a mold on a powder molding machine to obtain a circular ring-shaped blank, the pressing pressure is set to 40 MPa, and the pressure is maintained for 3 minutes to ensure that the density of the circular ring-shaped blank is uniform, and the specifications of the blank are φ25×15×7.5 mm; the blank is transferred to a sintering furnace for sintering at a temperature of 1250°C for 2 hours. After the sintering is completed, it is rapidly cooled to obtain a NiCuZn material with a high saturation magnetic flux density.
[0051] Example 9 The difference between this embodiment and embodiment 6 is that when preparing the high saturation magnetic flux density NiCuZn material, the preparation method of the high saturation magnetic flux density NiCuZn material includes the following steps: The main components and additives are mixed according to the formula ratio, wet sand milling is performed for 2 hours to obtain a mixture, and the mixture is pre-sintered at a temperature of 1000°C for 3 hours; secondary sand milling is performed in sequence to obtain a slurry, the slurry has a solid content of 66%, a slurry viscosity of 300 mPa·s, and a particle size after secondary sand milling of D50=0.5±0.1 μm; the slurry is spray granulated, and the granulated particles are pressed through a mold on a powder forming machine to obtain a circular ring-shaped blank, the pressing pressure is set to 40 MPa, and the pressure is maintained for 3 minutes to ensure that the density of the circular ring-shaped blank is uniform, and the specifications of the blank are φ25×15×7.5 mm; the blank is transferred to a sintering furnace for sintering at a temperature of 1300°C for 2 hours. After sintering, it is rapidly cooled to obtain a NiCuZn material with a high saturation magnetic flux density.
[0052] The experimental test results of Examples 8 to 9 are shown in Table 5.
[0053] Table 5 - Experimental test results of Examples 8 to 9 Result analysis: The difference between Examples 8 to 9 and Example 6 is that the preparation parameters are different when preparing the high saturation magnetic flux density NiCuZn material. Combined with the experimental test data in Table 5, it can be seen that the high saturation magnetic flux density NiCuZn material prepared by Example 8 has better comprehensive performance.
[0054] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. For those skilled in the art, without departing from the principle and spirit of the present application, various changes, modifications, substitutions and variants can be made to the embodiments, and these changes, modifications, substitutions and variants should all be included in the protection scope of the present application. Therefore, all equivalent changes made according to the structure, shape, and principle of the present application should all be included in the protection scope of the present application.
Claims
1. A high saturation magnetic flux density NiCuZn material, characterized in that: The high saturation magnetic flux density NiCuZn material includes a main component and an additive, wherein the main component includes Fe2O3 50.5-53.0mol%, ZnO 21.5-23.5mol%, NiO 22.5-24.5mol%, CuO 0.5-1.3mol%, and Mn3O4 0.5-2.2mol%; Based on the weight of the main component, the additives include: 0.10-0.30wt% glass powder, 0.01-0.10wt% talc, 0.05-0.10wt% titanium dioxide, 0.01-0.05wt% yttrium oxide, and 0.05-0.10wt% tin oxide.
2. The high saturation magnetic flux density NiCuZn material according to claim 1, characterized in that: The weight ratio of the Fe2O3 to the ZnO is 2.2-2.4:
1.
3. The high saturation magnetic flux density NiCuZn material according to claim 2, characterized in that: The weight ratio of the Fe2O3 to the ZnO is 2.3:
1.
4. The high saturation magnetic flux density NiCuZn material according to claim 1, characterized in that: Based on the weight of the main component, the additives include: 0.20wt% glass powder, 0.05% talc powder, 0.08wt% titanium dioxide, 0.04wt% yttrium oxide, and 0.08wt% tin oxide.
5. A method for preparing the high saturation magnetic flux density NiCuZn material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The main components and additives are mixed according to the formula ratio, wet sand milling is performed to obtain a mixture, the mixture is pre-sintered, and then secondary sand milling is performed to obtain a slurry. After the slurry is spray granulated and formed, it is sintered to obtain the high saturation magnetic flux density NiCuZn material.
6. The method for preparing the high saturation magnetic flux density NiCuZn material according to claim 5, characterized in that: The pre-sintering temperature is 950-1000°C.
7. The method for preparing the high saturation magnetic flux density NiCuZn material according to claim 6, characterized in that: The pre-sintering temperature is 980°C.
8. The method for preparing the high saturation magnetic flux density NiCuZn material according to claim 5, characterized in that: The solid content of the slurry is 60-66%, the viscosity of the slurry is 200-300 mPa·s, and the particle size D50 is 0.5±0.1 μm.
9. The method for preparing the high saturation magnetic flux density NiCuZn material according to claim 5, characterized in that: The sintering treatment temperature is 1200-1300°C.
10. The method for preparing the high saturation magnetic flux density NiCuZn material according to claim 9, characterized in that: The sintering temperature is 1250°C.
Citation Information
Patent Citations
Soft magnetic material and preparation method thereof
CN104230324A
Nickel-zinc ferrite material having high saturation magnetic flux density, high direct current superposition, and high Curie temperature, and preparation method thereof
CN104402424A
NiCuZn ferrite material and manufacturing method thereof
CN105198396A
Low-temperature sintered NiCuZn material with high magnetic conductivity and high Curie temperature and preparation method
CN118125817A
High initial magnetoconductivity, low-loss NiZn ferrite material and its preparation process
CN1861546A